2017
DOI: 10.1097/md.0000000000008149
|View full text |Cite
|
Sign up to set email alerts
|

SCN11A variants may influence postoperative pain sensitivity after gynecological surgery in Chinese Han female patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It is now known that there are nine voltage-gated sodium channel subtypes along with numerous splice variants. Of note, three of these isotypes: Na V 1.7 16,17 , Na V 1.8 [18][19][20] , and Na V 1.9 21,22 have been found to be principally expressed in primary afferent nociceptors. The relevance of these isotypes to human pain has been suggested by the observation that a loss-of-function mutation in Na V 1.7 (SCN9A) leads to congenital insensitivity to pain (CIP), a rare genetic disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that there are nine voltage-gated sodium channel subtypes along with numerous splice variants. Of note, three of these isotypes: Na V 1.7 16,17 , Na V 1.8 [18][19][20] , and Na V 1.9 21,22 have been found to be principally expressed in primary afferent nociceptors. The relevance of these isotypes to human pain has been suggested by the observation that a loss-of-function mutation in Na V 1.7 (SCN9A) leads to congenital insensitivity to pain (CIP), a rare genetic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is not clear that such antibodies can gain access to the appropriate Na V 1.7 channels and yield a reliable block of their function. Consequently, in spite of preclinical studies demonstrating that decreased Na V 1.7 activity leads to a reduction in inflammatory and neuropathic pain [16][17][18][19][20][21][22]37 , no molecule targeting this gene product has reached the final phase of clinical trials 32 . We therefore took an alternative approach by epigenetically modulating the expression of Na V 1.7 using two genome engineering tools, clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 (CRISPR-Cas9) and zinc-finger proteins (ZFP), such that one could engineer highly specific, long-lasting and reversible treatments for pain.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified two SNPs (rs33985936, rs11709492) were associated with inadequate analgesia. The mutation of rs33985936 (2725C > T) causes amino acid substitution Val909Ile which leads to the changes in intermolecular force of Nav1.9 [17]. Previous study reported that subjects who carrying the minor allele of rs33985936 were more sensitive to pain, while patients carrying the minor allele of rs11709492 have lower pain sensitivity [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, except for OPRM1, ABCB1, UGT2B7, and P2RX7, we selected other 14 genes known to be involved in systems related to pain perception and modulation based on evidence in the literature. The selected genes have been related to the ion channels (SCN9A, SCN10A, SCN11A, KCNJ6, TRPV1, and CACN A1E) [15][16][17][18][19][20], dopaminergic system (COMT, DRD2) [21,22], purinergic receptor (P2RY12) [23], adrenergic receptor (ADRB1) [24], estrogen receptor (ESR1) [25], serine/ threonine kinase (TAOK3) [26], growth factors (TGFB1) [27], and transcription factor (CREB1) [28]. The aim of the present study was to evaluate the association of common SNPs among aforementioned genes with the inadequate analgesia after single-port VATS.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, except for OPRM1, ABCB1, UGT2B7, and P2RX7, we selected other 14 genes known to be involved in systems related to pain perception and modulation based on evidence in the literature. The selected genes have been related to the ion channels (SCN9A, SCN10A, SCN11A, KCNJ6, TRPV1, and CACNA1E), [15][16][17][18][19][20] dopaminergic system (COMT, DRD2), [21,22] purinergic receptor (P2RY12),[23] adrenergic receptor (ADRB1), [24] estrogen receptor (ESR1), [25] serine/threonine kinase (TAOK3), [26] growth factors (TGFB1), [27] and transcription factor (CREB1). [28] The aim of the present study was to evaluate the association of common SNPs among aforementioned genes with the inadequate analgesia after single-port VATS.…”
mentioning
confidence: 99%